Gaya Berpacaran Remaja di Sekolah Menengah Atas Kota Blitar - Triana Setijaningsih (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2015)
Dating is the period between the approaches of the two opposite sex individuals, characterized by mutual personal recognition both strengths and weaknesses of each individual. The purpose of the research is to describe the style of adolescence dating in Senior High School Blitar. The method in this research uses descriptive design. The population in this research is the students of Catholic Senior High School Blitar, academic year 2013/2014 aged 17-19 years, a great samples taken is as much as 74 students using systematic random sampling technique. Data collecting is done proving questionnaires. Times data retrieval is performed on 11 to 31 March 2014. Data categorized using the formula according Sutomo by the cut of point, and explained with statistic techniques mode. The result of this research showed the most demanding style adolescence is intimate as 88%. The amount of any teen dating stle is at most two kinds of style as much as 42%. So that adolescence have a relationship that is based on the style of sincerity, warmth, intimacy between opposite sex to maintain a longstanding love affair. Need to do further research on the factors that influence the style of adolescence in dating.